Understanding of mathematical concepts through cooperative learning, and learning styles - Virgana Virgana (Intelektual Pustaka Media Utama, 2019)
The results of the mathematics learning of junior high school students have not been satisfactory. This is due to the low understanding of students' mathematical concepts. The purpose of this research is to identify the influence of cooperative learning model and learning style towards the understanding of the mathematical concepts of Junior High School students. The method is factorial experiments with 2 x 3 and sample of the study is 60 students of 8th grade junior high school. The analysis results of variance (ANOVA) indicate the following: the use of cooperative learning model of type Student Team Achievement Division influenced the understanding of the mathematical concepts significantly, there is an significant influence of the learning style towards an understanding of mathematical concepts, and there is also a significant influence of the interaction of cooperative learning model of type Student Team Achievement Division and learning style towards the understanding of mathematical concepts. So it can be concluded that the cooperative learning model can improve understanding of students' mathematical concepts and learning styles is a individual differences of learning students in absorbing mathematics subject matter. We hope that this study can be beneficial for further research to improve student’s achievements in mathematics.